Marital satisfaction, perception of role in family decision-making and coping strategies of Filipino wife of interracial marriage - Erispe, Ma. Jovie I.
This is a descriptive study aimed to determine the following objectives: 1) to assess the marital satisfaction of Filipino wives of interracial marriage; 2)to evaluate their perception of roles in family decision-making; 3) to identify areas in family decision-making that they actively participate in; and 4) to determine their coping strategies. Fourty-nine (49) Filipino wives of interracial marriage participated in this study. A Likert type scale for each variable was used, namely: Comprehensive Marital Satisfaction Scale, Family Decision-Making Scale and Ways of Coping Scale. It was found out that the respondents in this study, are in the slightly below the average range of marital satisfaction, both spouse decide in financial-economic and socio-moral areas of family decision-making but Filipino wives take care one socio-moral aspect, which is decision regarding a sick family member. They use problem-focused coping, which is taking a concrete action to reduce stress in the situation than emotion-focused ways to coping.